Stigmasisasi “Perempuan Alat” di Borong, Manggarai Timur Ditinjau dari Perspektif Filsafat Karol Wojtyla - Suhardi, Akrimianus; Puplius Meinrad, Buru; Widyawati, Fransiska (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
Women workers in the entertainment sector, such as pubs, are particularly vulnerable to discriminatory treatment and stigmatization from society. This issue is also prevalent among women in Borong. This study explores the community's views in Borong, East Manggarai, regarding their perceptions of women pub workers through the lens of Karol Wojtyla's philosophy. Utilizing a qualitative method, data was collected through in-depth interviews with community members. The community's perspectives from the field research were then analyzed in the context of Wojtyla's philosophical thoughts on persona. The study found that women workers in Borong's pub entertainment sector do experience societal stigmatization. The most common stigma involves labeling them as "tool women," and categorizing them as "heavy equipment" or "light equipment." This stigmatization is highly detrimental to these women. According to Wojtyla, negative stigmatization contradicts the concept of humans as unique, valuable, and precious individuals. Labeling humans as "tools" opposes the idea of humans as individuals who embody personal subjectivity. Humans, as persons, are not objects, as in the cosmological view, but are someone, based on the personalistic view. In conclusion, the stigmatization of women as tools diminishes their dignity as unique and valuable individuals. This study recommends that citizens be educated to develop solidarity and sensitivity towards human dignity. They should become individuals who respect other human beings. The stigmatization of viewing women as tools must be eradicated to uphold the noble dignity of humans. Everyone needs to learn solidarity with all, including those considered weak.